Kontribusi Pelaksanaan Supervisi Kepala Sekolah dan Lingkungan Kerja dalam Meningkatkan Kinerja Guru Di SD N 1 Ngrompak Kecamatan Jatisrono Kabupaten Wonogiri Tahun Ajaran 2016/2017 - Pratiwi, Restu Catur, Drs. Suwarno, SH., M. Pd (2017)
The background of this study is the importance of the performance of teachers in the education process, and therefore the performance of teachers should be well and continue to rise. The aims of the research to find out : 1) To knowing the role of implementing of principal supervision and work environtment in improving teacher performance in public elementary school 1 ngrompak academic year 2016/2017. 2) to knowing the role of supervision in improving teacher performance in public elementary school 1 Ngrompak academic year 2016/2017. 3) to kowing the role of work environment in improving teacher performance in public elementary school 1 Ngrompak academic year 2016/2017. This research use total sampling technique and stratued sampling technique. The data collection technique used observation and questionaries. The data were analized by using qualitative research. Hypothesis test use multiple regression analysis , F test, and t test. In this research showed : 1) there are role of principal supervison and work environment in improving teacher performance in public elementary school 1 Ngrompak. that was indicated by Fcount > Ftable ( 10,481>4,74) and significant value < 0,05 (0,008 < 0,05). 2) There are role of principal supervision in improving teacher performance in public elementary school 1 Ngrompak. That was proved by tcount > ttable (4,393 >2,306) and significant value < 0,05 (0,003 < 0,05). 3) there are role or work environment in improving teacher performance in public elementary school 1 Ngrompak that was indicated by tcount > ttable (2,483 > 2,262) and significant value < 0,05 (0,042 < 0,05). The coefficient of determinated for 75%, which means that influance from combination of supervision of principal and work environment in improving teacher performance is 75% while the remaining 25% is influenced by other variables. Variabels supervision of principle give relative contribution of 84% and effective contribution of 63%. Variable of work environment give relative contribution of 15,90% and effective contribution of 11,925%. By compairing from relative contribution and effective contribution seems that variable of supervision of principal has more effect and dominant role in improving teacher performance than compared with work environment. Key word : supervison od principles, work environment, and teacher performance